Geography and future of stock exchanges: between real and virtual space. - Wójcik, D (Blackwell Publishing, 2007)
This paper aims to contribute to the debate on the future of stock exchanges and financial centres by focusing on two questions. First, whether, how, why, and which stock exchange activities are prone to concentration in financial centres? Second, are they prone to concentration in national or international financial centres? Through a detail-rich analysis of stock exchange activities, including trading system, as well as relationships with members, issuers, and investors, the paper suggests a framework for the geography of stock exchange activities based on two dimensions—proneness to concentration in a financial centre and proneness to international consolidation. With this framework, predictions are made about the future geography of stock exchange activities led by the argument that while significant geographical reconfigurations are likely to unfold, driven primarily by the development of international networks of stock market institutions, stock exchanges, and financial centres will remain crucially important for each other.